Evaluation of Patients with Irritable Bowel Syndrome Diagnosed by Clinical Rome Criteria (TAJ: Journal of Teachers Association, 2009)
Sixty four patients who met the clinical Rome criteria for Irritable Bowel Syndrome wereprospectively evaluated by hematological, biochemical, endoscopic and sonographic methods.Complete blood count, sedimentation rate (ESR), thyroid profile, urinalysis, chest skiagram werefound normal or yielded no useful information. Stool examination revealed 6 (9.4%) positive forova/cyst of parasites and 7(10.9%) showed bacterial growth on culture. Structural evaluation(double contrast x-ray of colon, flexible sigmoidoscopy, endoscopy of upper Gl tract abdominalsonography) revealed abnormalities including: polyp (1), colitis (2), peptic ulcer (7), gall stone(2). So hematological, biochemical and structural evaluation should not be routinely done in allpatients diagnosed by Rome criteria unless sinister symptoms of organic diseases are present.doi: 10.3329/taj.v16i2.3884TAJ December 2003; Vol.16(2): 62-64